Adaptive Fine-Grained Sharing in a Client-Server OODBMS a callback-based approach. - Zaharioudakis, Markos (ACM transactions on database systems.)
For reasons of simplicity and communication efficiency, a number of existing object-oriented database management systems are based on page server architectures; data pages are their minimum unit of transfer and client caching. Despite their efficiency, page servers are often criticized as being too retrictive when it comes to concurrency, as existing systems use pages as the minimum locking unit as well. In this paper we show how to support object-level locking in a page-server context. Several approaches are described, including an adaptive granularity approach that uses page-level locking for most pages but switches to object-level locking when finer-grained sharing is demanded. Each of the approaches is based on extending the idea of callback locking. We study the performance of these approaches, comparing them to both a pure page server and a pure object server. For the range of workload that we have examined, our results indicate that the adaptive page server provides very good performance, usually outperforming the pure page server and the other page-server variants as well. In addition, the adaptive page server is often preferable to the pure object server; our results provides insight into when each approach is likely to perform better.